2014
DOI: 10.3354/ab00565
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of Vasa gene expression pattern in adults of the Lusitanian toadfish Halobatrachus didactylus

Abstract: The Vasa gene is essential for germ cell development in eukaryotes. It encodes a RNA helicase, a member of the DEAD box protein family. Using the RACE method, we cloned the Vasa cDNA of the Lusitanian toadfish Halobatrachus didactylus, and analyzed quantitative and qualitative Vasa expression and its protein immunolocalization. We reported a main product of about 2.4 kb which encodes a protein of 615 amino acids, but other minority Vasa products were also identified by RACE-PCR. This gene is predominantly expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Our study also analyzed vasa gene expression, mainly involved in the migration and differentiation of primordium germ cells in vertebrates, including in teleost [54][55][56]. In males, vasa expression was significantly lower than in females at 140 dpb, aligning with histological observations, indicating a period of accelerated ovarian development in females.…”
Section: Discussionsupporting
confidence: 54%
“…Our study also analyzed vasa gene expression, mainly involved in the migration and differentiation of primordium germ cells in vertebrates, including in teleost [54][55][56]. In males, vasa expression was significantly lower than in females at 140 dpb, aligning with histological observations, indicating a period of accelerated ovarian development in females.…”
Section: Discussionsupporting
confidence: 54%
“…On the other hand, tissue distribution analysis in immature Dabry's sturgeons revealed that Advasa transcripts were predominantly found in the ovary and testis, and also detected in the liver, intestines, spleen, kidney, heart and brain. Low expression levels of vasa in the extragonadal tissues was described in rainbow trout (Yoshizaki et al 2000), European sea bass (Blazquez et al 2011), Senegalese sole (Pacchiarini et al 2013), tongue sole and Lusitanian toadfish (Ubeda-Manzanaro et al 2014). This was ascribed to Vasa helicase activity referring to translational regulation of mRNAs involved in the specification and differentiation of other tissue-specific cell types (Ikenishi and Tanaka 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Using RT-PCR and in situ hybridization, we demonstrated that ddx4 and dnd1 are specifically expressed in the gonads, particularly in germ cells. Similar specific expressions of ddx4 mRNA in the gonads have been demonstrated in rainbow trout [ 50 ], medaka [ 51 ], tilapia [ 30 ], gibel carp [ 52 ], rice field eel [ 53 ], Pacific bluefin tuna [ 54 ], carp [ 55 ], catfish [ 18 ], European seabass [ 56 ], rare minnow [ 57 ], Atlantic cod [ 58 ], Korean rockfish [ 59 ], Solea senegalensis [ 60 ], toadfish [ 61 ], Japanese flounder [ 20 ], brown-marbled grouper [ 31 ], striped catfish [ 7 ], and Mekong giant catfish [ 62 ]. Coincidentally, the specific expression of dnd1 in testes and ovaries was revealed in zebrafish [ 15 ], medaka [ 29 ], rare minnow [ 63 ], gibel carp [ 13 ], tambaqui [ 64 ], Atlantic salmon [ 65 ], and starry flounder [ 21 ].…”
Section: Discussionmentioning
confidence: 99%